Fast-food-based hyper-alimentation can induce rapid and profound elevation of serum alanine aminotransferase in healthy subjects. Issue 5 (14th February 2008) - Kechagias, S; Ernersson, Å; Dahlqvist, O; Lundberg, P; Lindström, T; Nystrom, F H; ,
Abstract : Objective: To study the effect of fast-food-based hyper-alimentation on liver enzymes and hepatic triglyceride content (HTGC). Design: Prospective interventional study with parallel control group. Setting: University Hospital of Linköping, Sweden. Participants: 12 healthy men and six healthy women with a mean (SD) age of 26 (6.6) years and a matched control group. Intervention: Subjects in the intervention group aimed for a body weight increase of 5–15% by eating at least two fast-food-based meals a day with the goal to double the regular caloric intake in combination with adoption of a sedentary lifestyle for 4 weeks. Main outcome measures: Weekly changes of serum aminotransferases and HTGC measured by proton nuclear magnetic resonance spectroscopy at baseline and after the intervention. Results: Subjects in the intervention group increased from 67.6 (9.1) kg to 74.0 (11) kg in weight (p<0.001). Serum ALT increased from 22.1 (11.4) U/l at study start to an individual mean maximum level of 97 (103) U/l (range 19.4–447 U/l). Eleven of the 18 subjects persistently showed ALT above reference limits (women >19 U/l, men >30 U/l) during the intervention. Sugar (mono- and disaccharides) intake during week 3 correlated with the maximal ALT/baseline ALT ratio (r = 0.62, p = 0.006). HTGC increased from 1.1 (1.9)% to 2.8 (4.8)%, although this was not related to the increase in ALT levels. ALT levels were unchanged in controls. Conclusion: Hyper-alimentation per se can induce profound ALT elevations in less than 4 weeks. Our study clearly shows that in the evaluation of subjects with elevated ALT the medical history should include not only questions about alcohol intake but also explore whether recent excessive food intake has occurred.